"Big data" needs an analysis of decision processes. Issue 1 (26th February 2014) - Analytis, Pantelis P.; Moussaïd, Mehdi; Artinger, Florian; Kämmer, Juliane E.; Gigerenzer, Gerd
Abstract We demonstrate by means of a simulation that the conceptual map presented by Bentley et al. is incomplete without taking into account people's decision processes. Within the same environment, two decision processes can generate strikingly different collective behavior; in two environments that fundamentally differ in transparency, a single process gives rise to virtually identical behavior.